Identification and quantification of multi-class veterinary drugs and their metabolites in beef using LC–MS/MS. (15th July 2022) - Jung, Young Sung; Kim, Dan-Bi; Nam, Tae Gyu; Seo, Dongwon; Yoo, Miyoung
Graphical abstract: Highlights: A robust method is proposed for veterinary drugs (VDs) and their metabolites. Enhanced matrix removal-lipid is most advantageous sorbent for multi-class VDs. The heatmap provides a visual path to selecting the acceptable sorbent for VDs. Oxolinic acid and ractopamine were detected in actual beef samples. Abstract: The practice of abusing antibiotics to improve livestock growth poses a threat to food safety. To prevent and regulate this, accurate monitoring of residual veterinary drugs (VDs) is required. A method based on QuEChERS with dispersive solid-phase extraction for the determination of multi-class VDs was investigated using selected product ions under optimized multiple reaction monitoring conditions. During the clean-up procedure, chitosan, octadecyl silica, primary-secondary amine, and enhanced matrix removal (EMR)-lipid were evaluated for simultaneous analysis of multi-class VDs in beef matrix. The EMR sorbent was most advantageous (113/115) compared to others, and showed a satisfactory recovery range (70.7–117.9%) except cefquinome (67.3%) and cefalonium (69.8%). This methodology can be used to detect oxolinic acid and ractopamine (27.4% and 88.0% of maximum residue limit, respectively) in real beef samples. We thus study propose a simple and fast analytical method for multi-class VDs for the future health of humans and animals.